Association of insulin and insulin-like growth factors with Barrett's oesophagus. Issue 5 (19th September 2011) - Greer, Katarina B; Thompson, Cheryl L; Brenner, Lacie; Bednarchik, Beth; Dawson, Dawn; Willis, Joseph; Grady, William M; Falk, Gary W; Cooper, Gregory S; Li, Li; Chak, Amitabh
Abstract : Background: It is postulated that high serum levels of insulin and insulin growth factor 1 (IGF-1) mediate obesity-associated carcinogenesis. The relationship of insulin, IGF-1 and IGF binding proteins (IGFBP) with Barrett's oesophagus (BO) has not been well examined. Methods: Serum levels of insulin and IGFBPs in patients with BO were compared with two separate control groups: subjects with gastro-oesophageal reflux disease (GORD) and screening colonoscopy controls. Fasting insulin, IGF-1 and IGFBPs were assayed in the serum of BO cases (n=135), GORD (n=135) and screening colonoscopy (n=932) controls recruited prospectively at two academic hospitals. Logistic regression was used to estimate the risk of BO. Results: Patients in the highest tertile of serum insulin levels had an increased risk of BO compared with colonoscopy controls (adjusted OR 2.02, 95% CI 1.15 to 3.54) but not compared with GORD controls (adjusted OR 1.55, 95% CI 0.76 to 3.15). Serum IGF-1 levels in the highest tertile were associated with an increased risk of BO (adjusted OR 4.05, 95% CI 2.01 to 8.17) compared with the screening colonoscopy control group but were not significantly different from the GORD control group (adjusted OR 0.57, 95% CI 0.27 to 1.17). IGFBP-1 levels in the highest tertile were inversely associated with a risk of BO in comparison with the screening colonoscopy controls (adjusted OR 0.11, 95% CI 0.05 to 0.24) but were not significantly different from the GORD control group (adjusted OR 1.04, 95% CI 0.49 to 2.16). IGFBP-3 levels in the highest tertile were inversely associated with the risk of BO compared with the GORD controls (OR 0.36, 95% CI 0.16 to 0.81) and also when compared with the colonoscopy controls (OR 0.40, 95% CI 0.20 to 0.79). Conclusions: These results provide support for the hypothesis that the insulin/IGF signalling pathways have a role in the development of BO.